Convalescent Plasma Coupled With Medications for the Treatment of a Severe COVID-19 Patient: Drugs Analysis and Pharmaceutical Care Based on the Newly Established Guidelines for COVID-19 Remedy - Wang, Ying; Zhang, Yang; Yu, Qian; Zhu, Kun (Frontiers in Pharmacology, 2020)
Given the extreme importance of the current pandemic caused by COVID-19, and due to the fact that scientists agree that there is no identified treatment. We analyzed the treatment process of a COVID-19 patient cured with convalescent plasma coupled with medications, and summarized the therapeutic strategies to provide references for clinical front-line personnel.